Making a monster: Jesse Pomeroy, the boy murderer of 1870s Boston - Keetley, Dawn (University of Massachusetts Press, 2017)
Preface -- Chronology -- Introduction: Becoming monstrous -- Crimes -- On trial -- "The mark of the meat market" -- "Dime novel Pomeroy" -- "A moral monster" -- The scourge of smallpox -- Epilogue. Abused as a child? -- Notes -- Index